Determinants of postharvest losses among high moisture content vegetables traders in Kenya - Ndirangu, S Njuguna; Kanali, Christopher; Mutwiwa, Urbanus; Kituu, Gareth; Kamwere, Michael; Mung atu, Joseph (Journal of Postharvest Technology, 2017)
Food losses occur in the agricultural value chain due to internal and external factors. The study sought to identify the effects of some of these  factors in contributing to postharvest losses of vegetables in the traders component of the value chain. Both primary and secondary data were  utilized; the former was collected from retail and wholesale traders in 14 markets in four counties of Kenya. The selected counties were:  Kakamega and Kisii for indigenous vegetables, Kirinyaga for tomato and Kiambu for cabbages and kales. Age, urbanization, population,  female gender, use of appropriate infrastructure, value adding to produce through grading and sorting, access and use of market information,  had a negative relationship to losses. Losses were highest with cabbage, followed by tomatoes, Kales and lastly indigenous vegetables.  Vegetable sourced from the market had highest losses, followed by that from farmers groups, middlemen and the least being for that sourced at farmgate. Large batches, and longer times to sell and transport the produce led to high losses. Highest losses during transportation  occurred with the use of vehicles, followed by cycling, manual, draught and least with motocycle. The study recommends detailed study of the  effect of individual factors and their interrelation in contributing to food losses.
Keywords: Vegetables; traders,; postharvest losses,; factors,; quality.